THE INFLUENCE OF NUTRITIONAL INTERVENTION ON CHANGES IN KNOWLEDGE AND ATTITUDE OF MOTHERS OF UNDERNUTRITIONED CHILDREN IN THE WORKING AREA OF MANUTAPEN PUSKESMAS - Christine Natalia PS Lehot,; Christina Olly Lada,; Pius Weraman,; Anderias Umbu Roga,; Lewi Jutomo, (International Journal of Social Science, 2025)
Nutrition education for mothers and caregivers of toddlers is one of Unicef Indonesia's recommendations to alleviate the problem of stunting, malnutrition and undernutrition in Indonesia. Nutrition education can be done individually or in groups. From the research that has been done, the nutritional education intervention method is proven to be able to increase the knowledge, attitudes, and behavior of mothers of toddlers. Objectives: This study aims to study the effect of nutrition education interventions on improving knowledge and changing attitudes in the form of feeding practices for undernourished mothers at the Manutapen Health Center. Methods: This study used a quasi-experimental design with one group design, with a total sample of 20 respondents. The research instrument used a questionnaire and used the Wilcoxon Signed Rank. Results: The results of the non-parametric analysis using the Wilcoxon Signed Ranks test showed that there were significant differences in the knowledge of mothers before and after receiving nutrition education. This is indicated by the significant value of mother's knowledge before and after nutrition education of 0.000 <0.05. Likewise with the attitude of the mother, there was a significant difference in the attitude of the mother before and after receiving nutrition education. This is indicated by the significant value of the mother's attitude before and after nutrition education of 0.000 <0.05. Conclusions: The research results show that there is an influence of nutrition education in the form of counseling and mentoring through short messages on increasing knowledge and changing behavior